Integrated Organic Pyroelectric Sensors - Mustafayev, M.M. (Herald of Azerbaijan Engineering Academy, 2025)
Organic pyroelectric sensors employing poly (vinylidene fluoride–trifluoroethylene) [P(VDF-TrFE)] were fabricated and comprehensively characterized to realize a mechanically flexible and electronically integrable infrared-detection platform. Through a γ-butyrolactone – based sol–gel synthesis followed by controlled thermal annealing, highly crystalline β-phase copolymer films were achieved on PET substrates. Ferroelectric hysteresis characterization exhibited a coercive field of approximately 80 MV m⁻¹ and a saturation polarization close to 200 MV m⁻¹, indicative of pronounced dipole alignment and stable remanent polarization. Optimization of the poling conditions – specifically electric fields near 150 MV m⁻¹ and temperatures around 130 °C – resulted in significantly enhanced pyroelectric voltage and current outputs. Frequency-domain analysis demonstrated excellent correspondence with theoretical RC-network predictions, delineating distinct cut-off behaviors for current- and voltage-mode operation. Furthermore, the incorporation of a graphite absorber layer, in conjunction with square-wave laser modulation, markedly increased thermal-to-electrical conversion sensitivity. Collectively, these findings substantiate the feasibility of low-temperature, solution-processable fabrication routes for organic pyroelectric devices, providing exceptional mechanical compliance and seamless integration with organic thin-film transistor (OTFT) readout circuitry. This platform establishes a promising route toward scalable, large-area, and conformable infrared-sensing architectures suited for next-generation flexible electronic systems.